2016
DOI: 10.1590/2317-6369000122415
|View full text |Cite
|
Sign up to set email alerts
|

Ações em Saúde do Trabalhador desenvolvidas na Atenção Primária no município de Chapecó, Santa Catarina

Abstract: ResumoObjetivo: conhecer as ações de Saúde do Trabalhador desenvolvidas nos centros de saúde da Atenção Primária do município de Chapecó (SC) e verificar se elas estão incorporadas às rotinas dos serviços de saúde da Atenção Primária.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
0
5
1
13
Order By: Relevance
“…Seventy-nine percent of the teams report that they always or almost always try to find out user occupations, and 68% mentioned trying to better understand the characteristics of these occupations and the activities performed. It is interesting to note that this differs from the findings of Silva et al 15 , who looked at Primary Care Team practices in the city of Chapecó and found that not recognizing users as workers to be one of the largest hurdles for incorporating occupational health activities in the day-to-day activities of the teams.…”
Section: Diagnostic Of the Occupational Health Situationcontrasting
confidence: 90%
“…Seventy-nine percent of the teams report that they always or almost always try to find out user occupations, and 68% mentioned trying to better understand the characteristics of these occupations and the activities performed. It is interesting to note that this differs from the findings of Silva et al 15 , who looked at Primary Care Team practices in the city of Chapecó and found that not recognizing users as workers to be one of the largest hurdles for incorporating occupational health activities in the day-to-day activities of the teams.…”
Section: Diagnostic Of the Occupational Health Situationcontrasting
confidence: 90%
“…Entretanto, ainda são observadas poucas iniciativas para o atendimento de indivíduos fora do território-moradia, ainda que este seja o local aonde estes passam a maior parte do dia. Neste sentido, observa-se que apenas as notificações de agravos relacionados ao trabalho (acidentes de trabalho e doenças ocupacionais) são muitas vezes, as únicas ações voltadas para a saúde de trabalhadores na APS 17 .…”
Section: Discussionunclassified
“…In this respect, it is necessary to invest in human resource training and development that ensures access to up-to-date quality information on workers' health [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%